Технология низкокалорийных майонезов с растительными протеинами - Бахмач, Владимир Александрович; Бердашкова, Лилия Александровна; Носенко, Тамара Тихоновна (My University, 2015)
Thelow-calorie mayonnaise technology improvement with stabilization system "Stabileks" and vegetable protein products was studied in this work. Technological regimes were established for mayonnaise with 35% fat: the ratio of prescription components, temperature, conditions of emulsification and homogenization. There sults of obtained sample quality are presented. Usingof a stabilizer based on a miхture of hydrocolloid "Stabileks" with vegetable protein products had allowed to obtain mayonnaise with of high quality. Combining the formulations involving computer programs thus expanding the range of mayonnaises and sauces based on high quality raw materials. В работе изучалось совершенствование технологии низкокалорийного майонеза с использованием системы стабилизации «Стабилекс» и растительных белковых продуктов. Для майонеза 35% жирности установлены технологические режимы: соотношение рецептурных компонентов, температура, условия эмульгирования и гомогенизации. Приведены результаты качества полученных образцов. Использование стабилизатора на основе смеси гидроколлоида «Стабилекс» с продуктами растительного происхождения позволило получить майонез высокого качества. Комбинирование рецептур с использованием компьютерных программ, что расширяет ассортимент майонезов и соусов на основе высококачественного сырья.
Keywords: mayonnaise; майонез; emulsion; эмульсии; stabilizer; proteinproducts; properties; quality; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів